The influences of the TPS model and reading interests on writing skills of explanatory text of class VIII student - Lidya Atsari; Agustina Agustina; Novia Juita (International Conferences on Educational, Social Sciences and Technology)
This research aims to describe the influences of TPS model and reading interest of class VIII student of SMP Negeri 31 Padang about their skills of writing explanatory text. This research type is quantitative research with 2x2 factorial experiment design. The population of this research is all students of class VIII SMP Negeri 31 Padan. The data collects by using two methods. The analysis and discussion of the data apply descriptive-analysis method in accordance with the concept of experimental research. Based on the research the writer concludes that from explanatory text writing, the students who have high reading interest and low reading interest whom applies TPS model have higher reading interest than the students that using conventional learning methods. Furthermore, there is no interaction between TPS model with reading interest in influencing the learning outcomes of the students' in explanatory text writing skills.